RUSSIAN RESEARCHERS ABOUT KHOREZM CARAVAN ROUTES (DURING THE PERIOD KHIVA KHANATE) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article examines the history of Khorezm caravan roads in the Russian historiography (the 70s of 16th and 19th centuries).